Economic analysis of biogas adoption technology by rural farmers: The case of Faisalabad district in Pakistan. (July 2017) - Abbas, Tahir; Ali, Ghaffar; Adil, Sultan Ali; Bashir, Muhammad Khalid; Kamran, Muhammad Asif
Abstract: This study attempts to estimate the economics of biogas plants in Faisalabad District and identify the factors affecting the adoption of biogas technology. The key stakeholders of the biogas plant are farmers. Primary data from 160 respondents having biogas plants of 4 m 3, 6 m 3, 8 m 3, 10 m 3, 15 m 3, 20 m 3 and 25 m 3 from villages in Faisalabad was collected through stratified random sampling, using questionnaires. A benefit-cost ratio (BCR) is employed to estimate the financial benefits. A Logit model is used to analyze the factors affecting adoption of biogas plants. Results showed that BCR values are greater than 1 for biogas plants of all sizes. The most feasible size for a plant is 10 m 3 because it fulfills the cooking needs of an average family. However, small farmers with plant size of 4 m 3 benefit more than large farmers. Moreover, biogas adoption is not only financially feasible but environment-friendly as well. We conclude that biogas technology can be popularized by developing effective motivation strategies such as awareness through public service advertizing, through print and electronic media and by adoption of models of biogas plants best suited to the conditions of rural people in Pakistan. This further highlights the demand for the required policy framework to promote such renewable energy adoption technologies by local government and agricultural institutions, researchers, and policy makers. Highlights: Economic analysis of biogas adoption technology is investigated in rural areas. Different sizes of biogas plants are analyzed using multiple models/methods. Small farmers with 4 m 3 plant size are in greater benefit than large farmers. Biogas adoption is economically, socially and environmentally feasible in rural areas.